2016
DOI: 10.1108/jtf-03-2015-0010
|View full text |Cite
|
Sign up to set email alerts
|

Inciting tourist accommodation managers to make their establishments accessible to people with disabilities

Abstract: Purpose The purpose of this paper is to report on the research carried out in Québec as part of a master’s degree for the IÉSEG School of Management on behalf of Kéroul, an organization whose mission is to make tourism and culture accessible to people with disabilities. Established over 30 years ago and active largely in Québec, Kéroul has observed a lingering reluctance on the part of tourism industry operators to meeting the needs of disabled visitors. In the research, we set out to answer the following ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 6 publications
0
17
0
Order By: Relevance
“…Some of these studies reported by the databases appeared in a language other than English; however, when the titles and abstracts were examined, they were discarded along with the rest because they dealt with issues not related to the objective of the study. One hundred thirty-eight (n = 138) papers were selected for a full-text review, of which 16 records [3,13,39,41,48,[78][79][80][81][82][83][84][85][86][87][88] satisfied the selection criteria proposed for this research. Figure 2 shows the total articles deleted and the reasons for their exclusion.…”
Section: Results Of the Bibliographic Searchmentioning
confidence: 99%
See 3 more Smart Citations
“…Some of these studies reported by the databases appeared in a language other than English; however, when the titles and abstracts were examined, they were discarded along with the rest because they dealt with issues not related to the objective of the study. One hundred thirty-eight (n = 138) papers were selected for a full-text review, of which 16 records [3,13,39,41,48,[78][79][80][81][82][83][84][85][86][87][88] satisfied the selection criteria proposed for this research. Figure 2 shows the total articles deleted and the reasons for their exclusion.…”
Section: Results Of the Bibliographic Searchmentioning
confidence: 99%
“…Eight studies [13,41,79,[84][85][86][87][88] showed moderate quality (representing 50% of the included studies). Seven studies [3,39,48,78,80,82,83] were rated as high quality. However, it should be noted that the studies that obtained the quality classification "high" had scores close to "moderate".…”
Section: Results Of the Assessment Of The Methodological Qualitymentioning
confidence: 99%
See 2 more Smart Citations
“…When tourists travel to unfamiliar places, they are more Communication of accessibility conditions susceptible to unforeseen events (Eichhorn et al, 2013). The slow adaptation of hospitality infrastructures to accessible tourism (Capitaine, 2016;Agovino et al, 2017) and the different stages of competitiveness of the countries mentioned in the Tourism Accessibility Index (Porto et al, 2019) increase the risks of disabled tourists encountering inappropriate facilities for their personal health conditions (McKercher and Darcy, 2018). In fact, the low participation of disabled people in travel experiences is connected to the perceived lack of accessibility, which strongly influences their motivation to travel (Cole et al, 2019).…”
Section: Literature Review Information Search For Accessible Destinationsmentioning
confidence: 99%